Pitrdeba-carita : Mahārājā Bāhādura Syara Yatīndramohana Ṭhākura, Ke. Si. Esa. Āi. mahodaẏera jībanī - Manoramā Debī, 1856-1935 (Mālaśrī Debī, 1935)
Biography, in verse, of Yatīndramohana Ṭhākura, 1831-1908, intellectual and philanthropist from Bengal.